Intrauterine retained fetal bony spicules: an unusual finding in a case of intestinal obstruction - Sridevi, R.; Nithiya, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Prolonged Intrauterine retention of the foetal skeleton has not been adequately reported. Ossification represents retained foetal bone following spontaneous, missed, incomplete, or therapeutic abortion after 12 weeks of gestation. Various theories on the existence of osseous tissue within the uterine cavity have arisen from the diagnostic spectrum. However, sporadic cases of osseous metaplasia of the endometrial stromal cells without prior pregnancy loss have been reported. We report the case of an 18-year-old woman with an obstetric score of abortion 1 who presented with an acute abdomen in a surgical casualty. Ultrasonography revealed intrauterine hyperechoic foci, suggestive of a chronic retained foreign body. CECT revealed tubo-ovarian abscess, peritonitis, and intestinal obstruction. This case highlights the impact of retained foetal bones on the potential health risk of women. Dilatation and curettage performed for hyperechoic foci in the uterine cavity revealed chronic retained intrauterine bony spicules which were later confirmed by histopathology.